"I Know You Don't Know I Know…" Children Use Second‐Order False‐Belief Reasoning for Peer Coordination. Issue 1 (14th July 2014) - Grueneisen, Sebastian; Wyman, Emily; Tomasello, Michael
<x xml:space="preserve">Abstract</x> Numerous studies have investigated children's abilities to attribute mental states, but few have examined their ability to recruit these abilities in social interactions. Here, 6‐year‐olds (N = 104) were tested on whether they can use first‐ and second‐order false‐belief understanding to coordinate with peers. Children adjusted their decisions in a coordination game in response to either their partner's erroneous belief or their partner's erroneous belief about their own belief—a result that contrasts with previous findings on the use of higher order "theory of mind" (TOM) reasoning at this age. Six‐year‐olds are thus able to use their higher order TOM capacities for peer coordination, which marks an important achievement in becoming competent social collaborators.